Drainage System Capacity Analysis with Storm Water Management Model (SWMM) at Cemarajaya Housing, Karawang Regency West Java - Suprapti Suprapti; Muhammad Hamzah (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: This study aims to determine the factors that cause inundation/flooding in Cemarajaya Housing, evaluate existing drainage channels and plan drainage channels for unbuilt blocks and analyze the capacity of the drainage system using the EPA SWMM 5.1 program. Design/methodology/approach: Based on the simulation results using SWMM, the subcatchment response shows that an average of 22.11 mm per subcatchment is infiltrated and the rest becomes runoff of 310.23 mm. Findings: The abrasion disaster that hit the north coast of Karawang, especially the village of Cemarajaya, had occurred from around 1990 to 2016 and the most severe occurred in three hamlets, so residents affected by the abrasion had to be relocated to a place far from the shoreline. The Department of Public Housing and Settlement Areas of Karawang Regency built a housing estate to relocate residents affected by the abrasion disaster. Research limitations/implications: In this housing, 299 units of infiltration wells were built because the calculated channel dimensions were not possible to build due to the limited land area of the road. Practical implications: The problem that occurs in the housing is that the area where the housing construction is located is in the yellow zone based on the Karawang City/Regency Sanitation Strategic (SSK) data in 2017, which is an area prone to inundation of 25% to 50%. Originality/value: This paper is originality Paper type: Research paper